Predictors of Health-Related Quality of Life and Influencing Factors for COVID-19 Patients, a Follow-Up at One Month - Chen, Ke-Yang; Li, Ting; Gong, Fang-Hua; Zhang, Jin-San; Li, Xiao-Kun (Frontiers in Psychiatry, 2020)
ABSTRACT Objective：To survey the health-related quality of life (HRQoL) and its influencing factors among patients with COVID-19 in their first medical follow up. Methods: All patients diagnosed with COVID-19 were discharged from 12 hospitals in Wenzhou, Zhejiang from Jan 17, 2020 to Mar 20, 2020. Prospectively collected and analyzed data included demographics, clinical symptoms, comorbidity, and chest CT imaging features at the first follow up, one month after discharge. All patients underwent the HRQoL evaluation with the Chinese version of Short-Form 36-item questionnaire (SF-36) as well as a general condition questionnaire. Factors associated with SF-36 were constructed using linear regression. Predictors of impaired physical component summary (PCS) and a mental component summary (MCS) were identified by logistic regression. Results: SF-36 demonstrated a significant difference in HRQoL in patients with COVID-19, except in physical function (PF), when compared to the general Chinese population (p<0.05). The multiple linear regressions demonstrated that age was negatively associated with PF, role physical (RP), but positively associated with vitality (VT) (p<0.05). PF, bodily pain (BP), and role-emotional (RE) were negatively associated with the female sex (p<0.05). For mental health, the clinical subtypes were significant associated factors (p < 0.05). Length of stay (LOS) was strongly negatively associated with RE and RP, and positively associated with VT (p< 0.05). Logistical regression revealed that non-obese overweight (OR 3.71) and obesity (OR 3.94) were risk factors for a low PCS and female sex (OR 2.22) was a risk factor for a low MCS. Conclusions: Health-related quality of life was poor among COVID-19 patients at the one-month follow-up. Patients suffered from significant physical and psychological impairment. Therefore, prospective monitoring of individuals exposed to SARS-CoV-2 is needed in order to fully understand the long-term impact of COVID-19, as well as to inform prompt and efficient interventions to alleviate suffering.